Bio-ethanol production from Jatropha curcus - Sujan, SMA; Jamal, MS; Asad, MA; Fakhruddin, ANM (Bangladesh Journal of Scientific and Industrial Research, 2019)
Separate hydrolysis and fermentation (SHF) were employed to produce bio-ethanol from the jatropha stem and husk. This study investigates the favorable condition required to improve yield of monomeric sugars. Substrate was pretreated physically at first through cutter mill and subsequently by ball milling. Acremonium cellulase and optimash BG hydrolyzed the pretreated sample into fermentable sugars. In condition of 10% substrate concentration, ball milling for 60 min and 4 FPU/g enzyme loading and optimum sugar yield were observed. By comparison, jatropha stem is more favorable feedstock compared to jatropha husk in terms of both inherent sugar composition and sugar yield in enzymatic saccharification (hydrolysis). Yeast Saccharomyces cerevisiae, capable of converting hexose sugars into ethanol,was utilized in fermentation step. It was possible to extract 0.14 L and 0.20 L of ethanol per kg of dry substrate-based jatropha husk and jatropha stem, respectively. Bangladesh J. Sci. Ind. Res.54(1), 39-46, 2019